Accuracy assessment of a three-dimensional model obtained using the LiDAR sensor of the iPhone 13 Pro Max - Yanchuk, Oleksandr; Shulgan, Roman; Trokhymets, Serhii; Sheremet, Nazarii (Geodesy and Cartography, 2025)
Scanning of an educational classroom was performed using the LiDAR sensor of the iPhone 13 Pro Max. Comparison was conducted between the lengths of lines and coordinates determined from the model scanned by the LiDAR sensor with precise data measured using the Leica TCR 405 ultra electronic total station and determined from the model created photogrammetrically from images captured with the Sony Cyber-shot DSC-RX100 camera. The Root Mean Square Error (RMSE) of distance and spatial positioning was calculated for the LiDAR-scanned model.